Muscle immobilization delays abrupt change in myoglobin saturation at onset of muscle contraction - Hisashi Takakura; Tatsuya Yamada; Yasuro Furuichi; Takeshi Hashimoto; Satoshi Iwase; Thomas Jue; Kazumi Masuda (Japanese Society of Physical Fitness and Sports Medicine, 2022)
Hindlimb immobilization (IM) produces a decrease in functional oxidative capacity as well as morphological changes in muscles. However, the effect of IM on the mechanism of O2 supply to mitochondria in muscle tissue during muscle contraction is unknown, especially the contribution of myoglobin (Mb) to mitochondrial respiration. This study investigated whether IM causes a delayed response of intracellular Mb saturation (SmbO2) and decreased muscle oxygen uptake (mVO2) due to elevated intracellular oxygen tension (PmbO2) in contracting muscles using a rat hindlimb perfusion model. Three-week IM decreased the O2 release rate from Mb at the onset of muscle contraction (IM: 3.2 ± 0.9 vs. control (Con): 7.5 ± 2.9 10-2 µmol g-1 min-1; p < 0.05) and state 3 of mitochondrial respiration in muscle tissue (IM: 0.021 ± 0.006 vs. Con: 0.030 ± 0.009 10-3 µM g-1 sec-1; p < 0.05). Despite the increase in mVO2, the steady-state level of SmbO2 was higher during muscle contraction in the IM group, resulting in elevated PmbO2 (IM: 4.2 ± 1.0 vs. Con: 2.1 ± 1.0 mmHg; p < 0.05). In conclusion, IM decreased the O2 release rate from Mb; this alteration could be associated with mitochondrial dysfunction. These changes within muscle cells may be related to the delayed tissue response seen with near-infrared spectroscopy at the onset of muscle contraction.